‘It’s like wallpaper’: Victim-blaming, sexual violence and the media - ROYAL, KATHRYN,ELIZABETH (2019)
Research has long established that the media is inaccurate in its portrayal of violence against women, including sexual violence. It has been found to blame victim-survivors of rape, and create excuses for perpetrators. Research has also established that victim-blaming beliefs and rape myths exist within a significant proportion of the general public, and within members of our criminal justice system. Until now, little research has examined the consequences of such coverage on victim-survivors of sexual violence. This research therefore fills this gap. A total of 23 semi-structured interviews, 8 with specialist sexual violence support workers and 15 with victim-survivors of sexual violence, were conducted. A number of consequences of media coverage were identified. This includes consequences for mental health, such as the triggering of PTSD symptoms, as well as consequences for identifying and reporting sexual violence. As well as this, an analysis of a high-profile case of sexual violence was also conducted. A total of 204 articles reporting upon Ched Evans’ retrial for rape in October 2016 were analysed against guidelines produced for journalists reporting on violence against women by the National Union of Journalists. This analysis found that guidelines were often ignored, replicating the inaccurate coverage that previous research has highlighted. However, adding to such research is the argument that victim-blaming is more subtle than it once appeared to be in news coverage, arguably making it harder to challenge. This thesis therefore makes an original contribution to knowledge by examining modern, high-profile coverage of sexual violence cases, and how this coverage affects victim-survivors